PHACES syndrome : case report and literature review - Roganović, Jelena (Array, 2009)
Abstract: The case of a 2-month-old female infant with PHACES syndrome is reported. PHACES represents a broad spectrum of congenital anomalies, including the following primary features: posterior fossa brain malformations, large facial hemangiomas, arterial anomalies, cardiac defects and aortic coarctation, eye abnormalities, and ventral developmental defects. The literature on this rare condition is reviewed